2021
DOI: 10.1097/gme.0000000000001862
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of black rice extract on obesity in obese postmenopausal women: a 12-week randomized, double-blind, placebo-controlled preliminary clinical trial

Abstract: Objectives: Postmenopausal obesity is a paramount health concern among older women. Black rice is a well-known pigmented rice variety with a higher anthocyanin content. Both in vitro and in vivo studies have demonstrated the effects of black rice on obesity. The present study aimed to investigate the effects of black rice extract (BRE) on obesity among obese postmenopausal women from Korea. Methods: This was a 12-week, randomized, double-blind, placebo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…H. Jang et al, 2012). A clinical study in postmenopausal Korean women also demonstrated that treatment with a dosage of 500 mg of BR could reduce the weight of total and visceral fat (Jung et al, 2021). Hepatotoxicity induced by gentamicin was also attenuated by an anthocyanin-rich fraction from riceberry (Arjinajarn et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…H. Jang et al, 2012). A clinical study in postmenopausal Korean women also demonstrated that treatment with a dosage of 500 mg of BR could reduce the weight of total and visceral fat (Jung et al, 2021). Hepatotoxicity induced by gentamicin was also attenuated by an anthocyanin-rich fraction from riceberry (Arjinajarn et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Active components including peroxisome proliferator activated receptor (PPARα), carnitine palmitoyl transferase (CPT1A), and acyl‐CoA oxidase (ACO) improve hepatic steatosis and insulin resistance in HF‐fed mice (Guo et al, 2007, 2012; H. H. Jang et al, 2012). A clinical study in postmenopausal Korean women also demonstrated that treatment with a dosage of 500 mg of BR could reduce the weight of total and visceral fat (Jung et al, 2021). Hepatotoxicity induced by gentamicin was also attenuated by an anthocyanin‐rich fraction from riceberry (Arjinajarn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 60 studies underwent double full-text review. Subsequently, 19 studies were excluded: 4 were excluded because of insufficient data presentation ( 56 59 ) and 15 were excluded because of inappropriate interventions ( 60 74 ). Finally, 41 studies were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review with meta-analysis of randomised clinical trials concluded that anthocyanin supplementation of 300 mg/day or less for 4 weeks was sufficient to lower body mass index and body weight, with the greatest decrease in people from the Middle East [ 233 ]. An extract from black rice mainly containing cyanidin 3-glucoside given to 47 obese postmenopausal Korean women for 12 weeks decreased lower trunk fat and total body fat percentage, possibly by reducing body fat accumulation and increasing lipolysis [ 234 ].…”
Section: Therapeutic Actions Of Anthocyanins In Chronic Diseasesmentioning
confidence: 99%